„Oświata polska 1944—1956. Wybór źródeł. Cz. 1: Lata 1944—1948”. [Wybór] Stanisław Mauersberg, Marian Walczak. Warszawa, Polskie Towarzystwo Pedagogiczne 1999, ss. 580. ISBN 83-7204-159-8. Cz. 2: Lata 1949—1956. [Wybór] Stanisław Mauersberg, Marian Walczak. Warszawa, Polskie Towarzystwo Pedagogiczne 2000, ss. 838. ISBN 83-7204-160-1 - Chmielewski, Witold (Chowanna, 2009)
Recenzja